Design and Analysis of Upper Limb Rehabilitation Robots with Fully-actuated Shoulder Joints - Wang Zhanli; Duan Zhifeng; Li Shuang; Gao Moyao; Pang Zaixiang (Jixie chuandong)
Aiming at the problem of rehabilitation training for hemiplegic patients with upper limb motor dysfunction caused by stroke, a fully-actuated five degrees of freedom upper limb exoskeleton rehabilitation robot for shoulder joint is designed. Firstly, based on the principles of ergonomics and rehabilitation medicine, the degree of freedom of the upper limbs and the range of motion of each joint are determined, and the structure of the upper limb rehabilitation robot is designed. Secondly, the kinematics model of the upper limb rehabilitation robot is established and the kinematics equation is derived. Finally, the kinematics simulation analysis and work space analysis of the designed upper limb rehabilitation robot are carried out, and the two motion forms of shoulder joint adduction/abduction are compared and analyzed. The simulation results show that the joint movement is stable, the torque fluctuation is small, the robot has no excessive impact on the arm, the time for the robot to perform shoulder joint adduction/abduction movement is reduced, the rationality of the design of the upper limb rehabilitation robot and the convenience of the rehabilitation process are verified.